Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Section 5.4 - Adding and Subtracting Polynomials - Practice - Page 369: 5



Work Step by Step

$(4x^{3}-10x^{2}+1)-(-4x^{3}+x^{2}-11)$ Change the sign of every term inside the second parentheses: $(4x^{3}-10x^{2}+1)+(4x^{3}-x^{2}+11)=...$ Remove the both parentheses: $...=4x^{3}-10x^{2}+1+4x^{3}-x^{2}+11=...$ Simplify by combining like terms: $...=(4+4)x^{3}-(10+1)x^{2}+11+1=...$ $...=8x^{3}-11x^{2}+12$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.